Pengaruh Larutan Fixer terhadap Kualitas Pewarnaan Biopigmen Rumput Laut Eucheuma sp. sebagai Pengganti Pewarna Sintetis pada Tekstil [The Influence of Fixer for The Quality of Coloring Biopigmen Eucheuma sp. as a Subtitute for Synthetic Dyes in Textiles] - Sri Subekti; Achmad Amarudin; Moch Amin Alamsjah (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Seaweed Eucheuma sp. is one of the natural resources of Indonesia. Seaweed many processed in dry form after going through a drying process or processed into food ready for consumption. Seaweed is no longer just eaten or used to direct treatment, but can be processed into jelly, Algin, carrageenan (carrageenan) and furselaran (furcellaran) which is an important raw material in the food industry, pharmaceuticals, cosmetics and so on. This plant has an important economic value in various industries such as pharmaceutical, cosmetics, food, textile and paper industries. This study aims to determine the Fixer solution of Tawas, Poly Aluminium Chloride and Kapur Tohor most effective at biopigmen Eucheuma sp. instead of synthetic dyes in textile and determine the best concentration of the solution Fixer Tawas, Poly Aluminium Chloride and Tohor in deciding the color biopigmen Eucheuma sp. instead of synthetic dyes in textiles. This study uses a randomized block design (RAK). This research was conducted by observing and comparing the effect Fixer solution between Tawas, Poly Aluminium Chloride and Kapur Tohor against staining quality biopigmen seaweed Eucheuma sp. instead of synthetic dyes in textiles. Organoleptic test results showed fixation material Poly Aluminium Chloride able to maintain better color than the color produced by the fixation Tawas and Kapur Tohor. Poly Aluminium Chloride fixation material produces a bright brown color, Tawas brown, reddish brown Tohor. The test results of color fastness to rubbing cloth (dry) indicates that the color fastness of the strongest to the weakest sequentially generated from Tawas fixation materials, lime Tohor, Poly Aluminium Chloride, while the test fastness to washing soap and desecration of white cloth from the strongest to The weakest is Poly Aluminium Chloride, Kapur Tohor and Tawas.